PROFESIONALISME WARTAWAN AGAMA DI TVRI JAWA BARAT - Saifal saifal (AdZikra : Jurnal Komunikasi & Penyiaran Islam, 2021)
Abstrak Kemajuan zaman seiring dengan perkembangan industri media televisi yang begitu pesat. Perkembangan teknologi ini mengubah cara kerja para pekerja media khususnya di televisi. Kecepatan dalam mengirimkan hasil liputan para jurnalis langsung dari lapangan dan masyarakat bisa menonton kejadian tersebut secara langsung dengan proses live report. Live report sudah tidak asing lagi bagi para jurnalis, Yang udah satu bulan dimana banyak kegiatan menarik untuk diliput yaitu pada bulan suci Ramadan. Kegiatan di bulan suci Ramadan menarik untuk diliput sejak awal penentuan Ramadan hingga penentuan 1 Syawal. Persoalan yang muncul menjadi fokus penelitian ini, yang terkait dengan profesionalisme wartawan agama di TVRI Jawa Barat saat meliput kegiatan-kegiatan keagamaan khususnya di bulan Ramadan. Untuk menjawabnya dalam penulisan ini bedanya dengan pendekatan fenomenologi, tradisi penelitian kualitatif. Gulali wawancara mendalam dan pengamatan langsung di lapangan dengan narasumber wartawan TVRI Jawa Barat. Hasilnya menentukan wartawan agama di TVRI Jawa Barat secara garis besar sudah profesional. Namun ada beberapa catatan bagi wartawan junior di mana masih harus lebih banyak belajar untuk memahami kode etik jurnalistik dan istilah agama di bulan suci Ramadan. Kata kunci : Profesionalisme, Wartawan Agama, TVRI Jawa Barat Abstract The progress of the times is in line with the rapid development of the television media industry. The development of this technology has changed the way media workers work, especially on television. The speed in sending the reports of journalists directly from the field and the public can watch the incident directly with the live report process. Live reports are familiar to journalists. It's been a month where many interesting activities have been covered, namely during the holy month of Ramadan. Activities in the holy month of Ramadan are interesting to cover from the beginning of the determination of Ramadan to the determination of 1 Shawwal. The problems that arise are the focus of this research, which are related to the professionalism of religious journalists at TVRI West Java when covering religious activities, especially in the month of Ramadan. To answer it in this paper, it is different from the phenomenological approach, the tradition of qualitative research. Gulali in-depth interviews and direct observations in the field with TVRI journalists from West Java. The results determined that religious journalists at TVRI West Java were generally professional. However, there are some notes for junior journalists where they still have to learn more to understand the journalistic code of ethics and religious terms in the holy month of Ramadan. Keywords: Professionalism, Religious Journalists, TVRI West Java